دور المعتز لة و ادوارهم فى وضع اسس علم البلا غة وتطوير بحثه - Muhammad Husni Tamrin (Buletin Al-Turas, 2010)
This article focuses Balaghah (rethoric) which objectiv is to express the beauty of spoken and written  words. This science had developed since Jahiliyah period (pre-Islam) and continued to grow during the Islamic era. Among many groups developed the science, there was Mu'tazilah with the members such as Bisyr ibn Mu'tamir, al Jahiz, and Zamakhsyari. This groups is known as the adherents of schoolof rational since they put ratio first before texts(nash al-Qur'an and Hadis). They developed this science for propaganda and to confirm their throughts. According to Bisyr there are three requirements for the level of sentences beauty in Balaghah: pronunciation must be clear, easy to be understood, and use qafiyah (structured) well.